Psychometrics and Measurement Invariance of the Emotional and Behavioral Screener. (February 2014) - Lambert, Matthew C.; Epstein, Michael; Ingram, Stephanie; Simpson, Amy; Bernstein, Seth
Many students who exhibit behavioral and emotional problems during adolescence often show less severe problems in school in early grades. Screening for these early indicators can help educational professionals direct support to students who are more likely to benefit from increased support. The screening protocol needs to be psychometrically sound, accurate in identifying students at risk, and resource efficient. The present study explored the psychometric properties of a brief behavioral screener-the 10-item Emotional and Behavioral Screener (EBS)-for a sample of 5, 109 first-grade students assessed as part of a universal screening process. Confirmatory factor analysis and Rasch measurement techniques were used in conjunction to evaluate the factorial validity, item quality, rating scale functioning, and measurement invariance across gender of the EBS. Results indicated that the EBS has largely strong psychometric properties, with a few notable exceptions: potential multidimensionality, significant differential item functioning across gender, and only moderate differentiation between rating-scale categories (i.e., response options). Limitations and directions for research to clarify some remaining questions about this screening procedure are also discussed.